Dynamics of Ecological Issues Reflection in Semantic Content of Lexeme ‘zelenyy’ [green] (Dictionary Definitions and Associative Experiments) - G. M. Vasilyeva; M. V. Vinogradova (Научный диалог)
This article aims to identify the dynamics of the semantic scope of the lexeme ‘zelenyy’ [green] based on dictionary definitions and modern associative experiments. In the dictionaries of the XX century, the lexeme ‘zelenyy’ [green] was not associated with the semantic field of “Ecology”. However, in XXI century dictionaries, there is a tendency for the semantic derivative of this word to enter the sphere of designations for various phenomena related to environmental protection. A comparison of dictionaries’ associative norms from different years and modern associative experiments revealed a noticeable dynamic in the ecological component of the associative field of “Zelenyy” [Green]. Correlations between the dynamics of semantic processes and the linguistic consciousness of Russian students are traced. It is established that there is a leading expansion of the ecological component in linguistic consciousness compared to the dynamics of the word’s semantic scope. The differences found can be explained not only by external factors (ecological processes and changes in the state’s environmental policy) but also by value changes in the consciousness of the younger generation. The analysis of associative fields reveals a conceptual shift in the content of the word, namely, a transformation of its content from the sphere of physical objects and processes to the sphere of evaluative relationships. The ambivalent evaluation of the stimulus recorded in the modern experiment reflects the contradictory characteristics of the “green movement” and allows for predicting further derivational trends in the semantics of the lexeme ‘zelenyy’ [green].